Change in Some Chemical Parameters of two Environment Polluting Waste (Fertilizer Factory Effluent and Sweetmeat Factory Waste) Media After Culture of Three Important Microalgae - Toyub, MA; Miah, MI; Habib, MAB (Bangladesh Journal of Scientific and Industrial Research, 2008)
Some chemical parameters of fertilizer factory effluent (FFE) and sweetmeat factory waste (SFW) were analyzed before and after culture of three important microalgae (Spirulina platensis, Chlorella ellipsoidea and Scenedesmus obliquus) to make the waste environment friendly and to develop their economic use. Among the two wastes significantly (P<) higher phosphate phosphorus (116.09 mg/l), ammonia nitrogen (17.39), total suspended solids (TDS, 949.00 mg/l), total dissolved solids (28924.67 mg/l), total solids (30009.00 mg/l) and chemical oxygen demand (7892.00 mg/l) were in raw SFW. On the other hand significantly higher pH (7.51), nitrite nitrogen (19.65) and dissolved oxygen (0.33) were significantly higher in collected raw FFE. Before culture of S. platensis TDS of the prepared media were very high (10200.00 mg/l) due to addition of NaHCO3. Before inoculation of C. ellipsoidea and S. obliquus the highest TS, TSS, TDS and COD were recorded 867.28, 49.67, 771.33 and 1424.33 mg/l, respectively in prepared media. But after the culture of all the three microalgae, the amount of TS, TSS, TDS and COD were significantly (P<0.05) lower in all the media. The cultured microalgae were nutritionally rich. Key words: Chemical parameters, fertilizer factory effluent, sweetmeat factory waste, microalgae. Bangladesh J. Sci. Ind. Res. 42(3), 299-310, 2007